If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + 12y = 23 Solving X + 12y = 23 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-12y' to each side of the equation. X + 12y + -12y = 23 + -12y Combine like terms: 12y + -12y = 0 X + 0 = 23 + -12y X = 23 + -12y Simplifying X = 23 + -12y
| -3a-7a=-3a-6a+7 | | 8u+2-4(-3u+2)=4(u-1) | | 9z+4-8=27 | | M+8=2m+1 | | -2(4s-5)-10=-2(6s+2)-2 | | 2x(x-3)=1+4x | | t^2-6t-4=0 | | F(-3)=9x-5 | | 12X^2-48X+34=0 | | 9y+2x(5y-19)=38 | | .45x+.05(14-x)=.10(79) | | X+.4444=.75 | | 7x+12y=240 | | 1.5*e=6 | | 9y+2x(5x-19)=38 | | 5x-2(3x+5)=10x+32 | | 3p+5=-7+5p | | 5x-3y+12w+2y-4w+7x= | | 2(x-3)-9=6x-4(5+x) | | s+4-2i=0 | | X^2+y^2+4x-14y+4=0 | | 9y+2x(5-19)=38 | | 10+3k=4(8-6k)+5 | | -110=-7(-6m-4)+4m | | 7x-2=a | | 64=16*d | | x=0.6x+984 | | 2(f-6)=8 | | 384+0.6x= | | 12ab-4b=0 | | -10y+18=-(5y-7)+5y | | 23x=45 |